Update of the UP bikeways transport plan - Dizon, Miguel Martin M.; Patron, Erven Francis G.; Palmiano, Hilario Sean O. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
This non-motorized transport study aims to update the UP-Campus bikeway plan from the study conducted by the NCTS last 2008 entitled, Transportation and Traffic Management Plan for the University of the Philippines Diliman Campus, since the short and medium term plans of the study does not align with today's bikeway facilities. Specifically, it aims to estimate trips between in-campus locations, and then propose bikeway facilities from that data. Trip estimation will be done through the use of Origin-Destination Matrix and Desire Lines. While, the design of the bikeway facilities will include ideal placement of bike lanes and bike racks. These bikeway facilities are aimed to promote a new mode of transport for students' campus trips which has the potential to be faster, cheaper, and more environment-friendly.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Bicycle commuting -- Philippines -- Diliman (Quezon City).